A Scientist among the Sandstorms: Drought and the Discursive contexts of Francis Ratcliffe’s popular ecology - Russell, Arthur (Routledge: Taylor and Francis Group, 2008)
Flying Fox and Drifting Sand, British zoologist Francis Ratcliffe’s popular 1938 account of his ecological study of the problem of the fruit bat problem in Queensland and soil erosion in the arid pastoral areas of South Australia, is a prominent instance of an influential form of cultural critique in which scientists reflect publicly on the social, political and cultural interrelations and impacts of their disciplines. Notable in this genre are Aldo Leopold’s essay ‘The Land Ethic’, Rachel Carson’s Silent Spring, Paul Ehrlich’s The Population Bomb and, in the Australian context, Tim Flannery’s The Future Eaters. These text s are significant because they mix up the natural, social and cultural, and play a part in the emergence of ecocentric models of culture and society. Focusing on the ecological revision of the problem and concept of drought, this paper examines Ratcliffe’s popular ecology in relation to a significant articulation of scientific, literary, and political discursive practices at the time. Then, by establishing the international connections of this local instance, a picture is presented of the wider dispersal of this new articulation. It is argued that by specifying these practices and their interrelationship we can track a particular instance of the early emergence of ecologically inflected social theory.